The Effect of System Digitalization and Work Discipline on Employee Performance in the Business Operation Support Department of PT. Huawei - Kusjono, Gatot; Srirezeki, Ayu (Universitas Pamulang, 2025)
This study examines how the digitalization of systems and work discipline affects employee performance in the Business Operation Support Department of PT Huawei Indonesia. Using a quantitative survey method of 100 respondents, the analysis was carried out through linear regression with SPSS version 29. The findings showed that the digitization of the system had a significant effect (t=16.461>1.984; p=0.001) with the equation Y=8.186+1.293X1. Work discipline had a stronger impact (t=19.151>1.984; β=0.578; equation Y=2.353+1.703X2). Simultaneously, both variables contributed significantly (F=228.574>3.090; R²=82.5%; equation Y=-1.389+0.548X1+1.108X2), with work discipline as the dominant factor. The research emphasizes the importance of a balance between the implementation of digital technology and strengthening discipline for performance optimization.